7(w+3)=6(w-3)

Simple and best practice solution for 7(w+3)=6(w-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(w+3)=6(w-3) equation:


Simplifying
7(w + 3) = 6(w + -3)

Reorder the terms:
7(3 + w) = 6(w + -3)
(3 * 7 + w * 7) = 6(w + -3)
(21 + 7w) = 6(w + -3)

Reorder the terms:
21 + 7w = 6(-3 + w)
21 + 7w = (-3 * 6 + w * 6)
21 + 7w = (-18 + 6w)

Solving
21 + 7w = -18 + 6w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-6w' to each side of the equation.
21 + 7w + -6w = -18 + 6w + -6w

Combine like terms: 7w + -6w = 1w
21 + 1w = -18 + 6w + -6w

Combine like terms: 6w + -6w = 0
21 + 1w = -18 + 0
21 + 1w = -18

Add '-21' to each side of the equation.
21 + -21 + 1w = -18 + -21

Combine like terms: 21 + -21 = 0
0 + 1w = -18 + -21
1w = -18 + -21

Combine like terms: -18 + -21 = -39
1w = -39

Divide each side by '1'.
w = -39

Simplifying
w = -39

See similar equations:

| 36+3m=12m | | 2[4s-3]=18 | | -4x=16*5 | | -8(5+k)=-104 | | 5x-35=10x | | 1.3p+0.3-2=1.2 | | 19+2*10= | | z^2-1z=0 | | r+(-12)=-9 | | 3p^2+14p=5 | | 5(x+2)=3 | | 3c^2-18c=0 | | 9x-10=7x-16 | | p/7-2=15/3 | | 0.15+0.3w=0.93 | | 131*27= | | 5(8r-5s)+2r= | | -25x^2+4y^2-50x-125=0 | | -7+5W=-8(W+3) | | 27=-5x+7 | | 3+5(6x-x)=59 | | (2x+3)(2x+3)(2x+3)= | | 3x^4+3x^3-17x^2+x-6=0 | | 3+5(6x-6)=59 | | 2x^2y-8y= | | 2-(x+5)=3(3-x) | | 3q^2-12q+17=-0.25q^2+0.5q+1.75 | | 1.2r+3.6=14.4 | | 4y-9=29 | | 7x^4-29x^2+22=0 | | 0.8-0.4=0.9-0.5n | | 4(+8)=+20 |

Equations solver categories